High availability and disaster recovery : concepts, design, implementation. - Schmidt, Klaus, ....- (Berlin : Springer, 2006)
Companies and other organizations depend more than ever on the availability of their Information Technology, and most mission critical business processes are IT-based processes. Business continuity is the ability to do business under any circumstances and is an essential requirement modern companies are facing. High availability and disaster recovery are contributions of the IT to fulfill this requirement. And companies will be confronted with such demands to an even greater extent in the future, since their credit ratings will be lower without such precautions.Both, high availability and disaster recovery are realized by redundant systems. Redundancy can and should be implemented on different abstraction levels: from the hardware, the operating system and middleware components up to the backup computing center in case of a disaster. This book presents requirements, concepts, and realizations of redundant systems on all abstraction levels, and all given examples refer to UNIX and Linux systems.
Keywords: Computernetwerken